A Green Day: Embracing Climate Action - Prabha, Jyoti (Journal of Data Science, Informetrics, and Citation Studies)
The book serves as a deeply insightful narrative centered on the ecological journey and mission of several people who care for the environment. Their efforts represent a beacon of individual willpower translating into transformative ecological action. The book urges civil society organizations and communities to support and scale such missions to restore and preserve forest cover-symbolizing a broader call to heal Mother Earth.